DOCUMENTARY VIDEO DESIGN OF DAWAN BROWN SUGAR - Setiawan, I Kadek Guntur; Setiawan, I Nyoman Anom Fajaraditya; Pramawati, I Dewa Ayu Agung Tantri (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This study aims to design a documentary video that documents the process of making brown sugar in Dawan Village. The research methods used include collecting primary data through interviews and direct observation, as well as secondary data from related literature. The process of designing this documentary video includes several stages, namely pre-production, production, and post-production. In the pre-production stage, concept planning, script writing, and storyboarding are carried out. The production stage involves taking pictures and sound at the brown sugar production location. While the post-production stage includes video editing, adding sound effects, and compiling a narrative. The result of this study is a documentary video that is expected to provide comprehensive information about the brown sugar production process in Dawan, as well as increase public appreciation for this local product. This video is also expected to be an effective promotional media to introduce Dawan brown sugar to a wider market.